Efek Antihiperlipidemia Kombucha Daun Kari (Murraya koenigii (L.) Spreng) pada Tikus Putih Jantan (Rattus norvegicus) yang Diinduksi Dengan High Fat dan PTU - Hardyanto Napitupulu; Muharni Saputri; Salmah Handayani Lubis; Muflihah Fujiko; Ernawaty Ginting (Yayasan Penelitian dan Inovasi Sumatera, 2021)
Curry leaves (Murraya koenigii (L.) Spreng) is a plant that is often used in cooking spices that are high in fat because curry leaves contain secondary metabolite compounds such asalkaloids, glycosides, and flavonoids that serve to inhibit the growth of free radicals and lower cholesterol levels. Generally curry leaves are processed traditionally in a simple form, while research will process curry leaves in the form of fermented beverages in the form of kombucha tea. This study aims to explore the process of making curry leaf kombucha tea and know the antihiperlipidemia effect. This research is descriptive and experimental, including material collection, simplisia making, phytochemical screening, fermentation of curry leaf kombucha, evaluation of dosage quality, testing of triglyceride levels in rats with Electrode-Based Biosensor technique. The mice used in this study were 25 and divided into 5 test groups. K1 (negative blank), K2 (Simvastatin), K3 (dose 100 ml), K4 (dose 150 ml), K5 (dose 200 ml) induced using 80% egg yolk and PTU 0.2%. The results showed that the quality evaluation of kombucha tea gave good results to pH 3.08-3.44 and did not experience changes in taste and smell. In the group of 5 doses of 200 ml with kombucha tea administration on the 7th to 15th day, it was shown that cholesterol levels decreased from 253.0 mg/dL to 92.2 ml/dL where these results were close to comparing (simvastatin) from 247.8 mg/dL to 79.2 mg/dL